Outpatients' satisfaction and their loyalty towards public rural clinic / Mas 'udah Asmui - Asmui, Mas 'udah (2012)
Satisfaction is one of the paramount importance for health care providers (Tam, 2007) and a prime importance to quantify the competency of any health system worldwide (Sajid & Baig, 2007). This study is to investigate the satisfaction and loyalty among outpatients who received treatments in rural area clinic, Jengka Public Health Clinic, Pahang. It is also to find out the effectiveness of the health care services provided by the public rural clinic to their rural outpatients who were not highly educated and earning a low family income (less than RM2000 per month). With fewer complaints from the outpatients unlike urban outpatients, it is important to determine the satisfaction among older, married women, workers outpatients and their loyalty towards the clinic. As a result, the married women outpatients agreed and strongly agreed with the medical care satisfaction they received while the older outpatients felt uncertain and satisfied with the treatment. Nevertheless, majority of the outpatients will return to the clinic for future treatment since the medical treatment fee was low.